Electrolyte droplet spraying in H2 bubbles during water electrolysis under normal and microgravity conditions - Aleksandr Bashkatov; Florian Bürkle; Çayan Demirkır; Wei Ding; Vatsal Sanjay; Alexander Babich; Xuegeng Yang; Gerd Mutschke; Jürgen Czarske; Detlef Lohse; Dominik Krug; Lars Büttner; et al. (Nature Communications)
Abstract Electrolytically generated gas bubbles can significantly hamper the overall electrolysis efficiency. Therefore it is crucial to understand their dynamics in order to optimise water electrolyzer systems. Herein, we elucidate a distinct transport mechanism whereby electrolyte droplets are sprayed into H2 bubbles. These droplets arise from the fragmentation of the Worthington jet, which is engendered by the coalescence with microbubbles. The robustness of this phenomenon is corroborated under both normal and microgravity conditions. Reminiscent of bursting bubbles on a liquid-gas interface, electrolyte spraying results in a flow inside the bubble. This flow couples, in an intriguing way, with the thermocapillary convection at the bubble’s surface, clearly underlining the high interfacial mobility. In the case of electrode-attached bubbles, the sprayed droplets form electrolyte puddles affecting the dynamics near the three-phase contact line and favoring bubble detachment from the electrode. The results of this work unravel important insights into the physico-chemical aspects of electrolytic gas bubbles, integral for optimizing gas-evolving electrochemical systems.